Bedtime stories: The nightingale - B. Jain publishers (New Delhi : B. Jain publisher Ltd, 2012)
The emperor loves a nightingale's beautiful song. He replaces it with a shiny, fake bird. When he falls ill, the real nightingale returns and heals him. He learns that true beauty comes from the heart.
location: 3D
Keywords: Fiction book